Perilaku Efisiensi Energi Penghuni Rumah Susun Sederhana Sewa (Rusunawa) di DKI Jakarta - Gilang Dewi Rahayu; Maria Immaculata Ririk Winandari (Universitas Sebelas Maret Surakarta, 2025)
Energy Efficiency Behaviour of Low-Cost Rental Apartment (Rusunawa) Residents in DKI JakartaThe density and diverse housing, such as rusunawa, occupant behavior plays a critical role in determining the building operational efficiency. This study aims to explore the energy efficiency-related behavior of rusunawa occupants, focusing on the Daan Mogot and Tipar Cakung Rusunawa complexes. The research method employed is an exploratory case study using the Yin approach, based on qualitative data and field observations. The findings reveal that limitations in cross-ventilation, unit orientation, and natural lighting prompt occupants to modify their behavior, which in turn leads to increased energy consumption. Furthermore, the majority of occupants lack a theoretical understanding of energy efficiency concepts, with energy-saving practices occurring spontaneously through daily habits. Based on these findings, the integration of architectural design, occupant education, and participatory policies is essential for creating energy-efficient Rusunawa in Jakarta.